Design and analysis of liquid hydrogen storage tank for high-altitude long-endurance remotely-operated aircraft. (14th December 2015) - Xu, Weiqiang; Li, Qianqian; Huang, Minjie
Abstract: Liquid hydrogen is seen as an outstanding candidate for the fuel of high altitude, long endurance unmanned aircraft. The design of lightweight and super-insulated storage tanks for cryogenic liquid hydrogen is since long identified as crucial to enable the adoption of the liquid hydrogen. The basic structural design of the airborne cryogenic liquid hydrogen tank was completed in this paper. The problem of excessive heat leakage of the traditional support structure was solved by designing and using a new insulating support structure. The thermal performance of the designed tank was evaluated. The structure of the tank was analyzed by the combination of the film container theory and finite element numerical simulation method. The structure of the adiabatic support was analyzed by using the Hertz contact theory and numerical simulation method. A simple and effective structure analysis method for the similar container structure and point-contact support structure was provided. Bases for further structural optimization design of cryogenic liquid hydrogen tank were provided also. Research results showed that: the insulating support can reduce the heat leakage of the support structure more than 85%, while the maximum stress of point-contact supports structure can be 9 times larger than conventional support structure; the tank designed in this paper can meet the structural and thermal requirements for aerospace applications. Highlights: By designing an insulated support structure, the heat leakage of the support structure is reduced by more than 85%. Structural strength of the tank is calculated through film theory and checked by the numerical simulation of ANSYS. Both Hertz contact theory and ANSYS finite element simulation are applied to analyze the insulation support structure. Simple experiments are also conducted.